Environmental psychology: Challenges and opportunities for a sustainable future. Issue 5 (16th September 2022) - Benz, Alexander; Formuli, Arusu; Jeong, Garam; Mu, Nan; Rizvanovic, Nejra
Abstract: Recent ecological developments and in particular the risks of climate change have led to the emergence of new scientific challenges and fields. One field that has gained momentum over the past decades is environmental psychology. Researching and analyzing environmental phenomena it faces the challenges of connecting conceptual problems, the interdisciplinary use of languages and definitions, different understandings and the use of different methodologies, and the scientific explanation of such phenomena. This paper reflects on the challenges and also the opportunities for establishing a sustainable future from a psychological point of view. The topics addressed are a selection of criteria for adapting to changing environments, perspectives on how to harvest insights from different fields of scientific endeavor and ideas how to make use of the necessary interdisciplinarity. Furthermore, questions are raised concerning personal identity, cultural and spiritual values, the ethical aspects of decision‐making in a changing world, and the conceptual challenges facing sustainable ecological development.